PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN DENGAN GROUP COHESIVENESS SEBAGAI VARIABEL PEMODERASI - Lestari, Ni Kadek Rika; Wisadha, I Gede Suparta (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
This study aimed to determine the effect of budgetary participation on budgetary slack with group cohesiveness as a moderating variable. Method of data collection in all departments and agencies contained in the Tabanan Local Government Agencies with 23 SKPDs and total questionnaire by 69 respondents. Sampling is done by using purposive sampling method that consists of the head office, the head of finance department and the relevant department staff at the agency directly involved in the preparation and implementation of the budget and has been involved at least once in the preparation of the budget. Hypothesis testing is done with analytical techniques Moderated Regression Analysis (MRA). The result showed that budgetary participation significant and positive impact on budgetary slack, but the group cohesiveness has not been able to strengthen its influence between budgetary participation and budgetary slack.
Keywords: budgetary participation, budgetary slack, group cohesiveness